Note on the Invariance Properties of Operator Products Involving Generalized Inverses - Xiaoji Liu; Miao Zhang; Yaoming Yu (Abstract and Applied Analysis)
We investigate further the invariance properties of the bounded linear operator product AC1 B1 D and its range with respect to the choice of the generalized inverses X and Y of bounded linear operators. Also, we discuss the range inclusion invariance properties of the operator product involving generalized inverses.